2009
DOI: 10.1002/hep.22940
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of physical activity in patients with nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease, characterized by elevated liver enzymes, central obesity, and insulin resistance, is becoming increasingly prevalent. The effects of changes in physical activity on the metabolic profile of this group have not been reported. We assessed at 3 months the impact of a behavior change-based lifestyle intervention on physical activity and the effects of this change on the metabolic profile of people with fatty liver disease. In all, 141 participants with nonalcoholic fatty liver dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
206
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(223 citation statements)
references
References 40 publications
6
206
1
10
Order By: Relevance
“…2B). Several studies have reported indications for obtaining the direct effect of exercise on hepatic steatosis [6][7][8] ; exercise with less frequency and dose was found to be effective in both light and moderate volume exercise programs, 34 the PA volume of which was below the current guidelines for health promotion 35 and for managing body weight. 36 At present, scientific evidence for the benefits of PA and the optimal dose and modality for PA in NAFLD management is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Several studies have reported indications for obtaining the direct effect of exercise on hepatic steatosis [6][7][8] ; exercise with less frequency and dose was found to be effective in both light and moderate volume exercise programs, 34 the PA volume of which was below the current guidelines for health promotion 35 and for managing body weight. 36 At present, scientific evidence for the benefits of PA and the optimal dose and modality for PA in NAFLD management is limited.…”
Section: Discussionmentioning
confidence: 99%
“…3 With respect to physical activity (PA), recent reports on clinical outcomes have indicated that physical inactivity and low aerobic fitness are underlying reasons for the increased number of NAFLD cases, 4,5 and that both aerobic and resistance exercises have specific effects on NAFLD treatment in the absence of weight reduction. [6][7][8] We have recently proven the therapeutic effects of increased PA with or without dietary restriction in greatly reducing hepatic inflammation and the related oxidative stress levels outweigh those achieved by dietary restriction alone. 9,10 Thus, although there is an overall paucity of evidence on the benefits of PA as a treatment for NAFLD, management should include assessing PA levels and setting of lifestyle goals based on adopting regular exercise, with a focus on attaining sustainable PA habits.…”
mentioning
confidence: 99%
“…1 Concomitant with pharmacotherapy trials, there is increased interest in the efficacy of lifestyle interventions to reduce liver fat and steatohepatitis. [2][3][4][5] In this context, weight reduction and behavior therapy-based interventions have been reviewed in HEPATOLOGY, 6 but there is little information on the role and importance of physical activity in NAFLD.…”
mentioning
confidence: 99%
“…Although studies that have observed the efficacy in the treatment of NAFLD in human beings observed the concomitant reduction of 3 to 10% in body weight (Johnson et al, 2012), there is evidence that physical training is able to reduce the hepatic lipid levels by mechanisms independent of weight variation (George et al, 2009), once calorie readjustment after induced obesity did not appear to present benefits in the metabolic parameters, associated with insulin resistance, when physical training was not included (Estadella et al, 2004).…”
Section: Discussionmentioning
confidence: 99%